2023
DOI: 10.1186/s13033-023-00594-7
|View full text |Cite
|
Sign up to set email alerts
|

Co-producing research on psychosis: a scoping review on barriers, facilitators and outcomes

C. E. Jakobsson,
E. Genovesi,
A. Afolayan
et al.

Abstract: Introduction Co-production is a collaborative approach to service user involvement in which users and researchers share power and responsibility in the research process. Although previous reviews have investigated co-production in mental health research, these do not typically focus on psychosis or severe mental health conditions. Meanwhile, people with psychosis may be under-represented in co-production efforts. This scoping review aims to explore the peer-reviewed literature to better underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Research led by those with lived experience of mental health inpatient care generally, and surveillance technologies specifically, would be particularly valuable in evaluating potential harms missed by academic or clinical researchers. Care should also be taken to ensure that the perspectives of those who are unwell, or may need support to express their views, are captured in any future research on technologies in these settings [90]. Further synthesis of data on surveillance from other locations where people with mental health problems present may be helpful, for example in crisis services or mental health presentations in emergency departments.…”
Section: Discussionmentioning
confidence: 99%
“…Research led by those with lived experience of mental health inpatient care generally, and surveillance technologies specifically, would be particularly valuable in evaluating potential harms missed by academic or clinical researchers. Care should also be taken to ensure that the perspectives of those who are unwell, or may need support to express their views, are captured in any future research on technologies in these settings [90]. Further synthesis of data on surveillance from other locations where people with mental health problems present may be helpful, for example in crisis services or mental health presentations in emergency departments.…”
Section: Discussionmentioning
confidence: 99%
“…We consider that CHAMPS was strengthened by its unique development process, using preference research to shape the intervention and involving individuals with lived experience as CHAMPS coproducers. Despite potential barriers to coproduction research, such as a high turnover rate of clinicians or researchers and stigma toward patients [ 65 ], our patient-partners anecdotally reported that the coproduction process was successful in building healthy relationships between coresearchers and patient-partners and provided opportunities for personal growth. Feedback from our co-researchers also highlighted the benefits, including the production of a well-informed intervention that valued the knowledge of all contributors.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it is unknown how frequent design studies specifically target people with psychotic symptoms and features. There is a scoping review of coproducing research on psychosis [ 7 ], but coproduction and design approaches are distinct methodologies. Design approaches facilitate designing initiatives that prioritize participants’ needs, expertise, and knowledge whereas coproduction facilitates collaborative delivery and knowledge production.…”
Section: Introductionmentioning
confidence: 99%